Physical, chemical characteristics and antioxidant activity of edible film whey with the addition of telang flowers extract (Clitoria ternatea .L) - Nabila, Syifa; Juliyarsi, Indri; Melia, Sri (Journal of Nutrition Science, 2024)
This study aims to obtain the effect of adding telang flower extract (Clitoria ternatea. L) on the edible whey film's physical and chemical properties and antioxidant activity. This research uses a randomised design group of 4 treatments and five working groups. Conducted on antioxidant activity and physical characteristics. The study's results obtained edible whey film with telang flower extract was 0.14 mm, moisture content of 16.14%, solubility time of 45.60 seconds, and water vapor transmission rate of 3.72 g/m2. day, met the standards of JIS 2019. has the highest B*(bluish) color test value of 6.50 and average antioxidant activity of 17.60% to 49.60%. Based on the research results, it can be concluded that adding telang flower extract (Clitoria ternatea L.) can act as an antioxidant in edible whey film.